Amelioration of Mouse Retinal Degeneration After Blue LED Exposure by Glycyrrhizic Acid-Mediated Inhibition of Inflammation - Kim, Gyu Hyun; Paik, Sun-Sook; Park, Yong Soo; Kim, Hyoun Geun; Kim, In-Beom (Frontiers in Cellular Neuroscience, 2019)
Glycyrrhizic acid (GA) is a major component in the root and rhizomes of licorice (Glycyrrhiza glabra), which have been used as an herbal medicine, because of its anti-inflammatory activity. GA is known as an inhibitor of high-mobility group box 1 (HMGB1), which in involved in the pathogenesis of various inflammatory diseases including inner retinal neuropathy. In this study, we examined the effect of GA in a mouse model of retinal degeneration (RD), the leading cause of blindness. RD was induced by exposure to a blue light-emitting diode (LED). In functional assessment, scotopic electroretinography showed that the amplitudes of both a- and b-waves were significantly reduced in RD mice (P < 0.05), whereas they were significantly increased in GA-treated RD mice (P < 0.05), compared to those in non-treated RD animals. In histological assessment, GA treatment preserved the outer nuclear layer where photoreceptors reside and reduced photoreceptor cell death. GA-treated retinas showed significantly reduced expression of proinflammatory cytokines such as TNF-α, IL-6, IL-1β, CCL2 and 6, iNOS, and COX-2 (P < 0.05), compared to that in non-treated retinas. Immunohistochemistry showed that Iba-1 and GFAP expression was markedly reduced in GA-treated retinas, indicating decreased glial response, retinal stress and inflammation. Interestingly, HMGB1 expression was reduced in non-treated RD retinas whereas GA increased its expression. These results demonstrate that GA reduces retinal inflammation by inhibiting HMGB1 release from photoreceptors in blue LED-induced RD and preserves retinal structure and function, suggesting that GA may have potential as a medication for the treatment of RD.